2016
DOI: 10.1039/c6ra07597e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of phenolic resin: new insights based on bond dissociation energy and reactivity of functional groups

Abstract: Based on bisphenol-F-like model molecules, the bond dissociation energies and Fukui function were calculated to interpret the relationship between the atomistic structure and thermal properties of the phenolic resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…For example, BDE values are used to predict relative reaction rates using well-established Evans-Polanyi-type correlations with bond strengths in radical hydrogen atom abstractions 2 . BDEs also provide insight into thermodynamically accessible reaction mechanisms for a given compound, and their calculation is often the first step in characterizing dominant pathways in combustion 3 , polymer synthesis 4 and thermal stability 5,6 , lignin depolymerization 7 , drug metabolism [8][9][10] , explosives 11 , organic synthesis planning 12,13 , and other applications to energy-related materials 14 .…”
mentioning
confidence: 99%
“…For example, BDE values are used to predict relative reaction rates using well-established Evans-Polanyi-type correlations with bond strengths in radical hydrogen atom abstractions 2 . BDEs also provide insight into thermodynamically accessible reaction mechanisms for a given compound, and their calculation is often the first step in characterizing dominant pathways in combustion 3 , polymer synthesis 4 and thermal stability 5,6 , lignin depolymerization 7 , drug metabolism [8][9][10] , explosives 11 , organic synthesis planning 12,13 , and other applications to energy-related materials 14 .…”
mentioning
confidence: 99%
“…Their increased occurrence can be explained by the symmetrical structure of Antioxidant 2246 and cleavage of the methylene bridge. It was found that the CC bond strength in methylene bridges of methanediyldiphenols is weakest in o‐o’ derivatives ( o ‐ o ’ < o ‐ p ’ < p – p ’) , and indeed the products are formed through benzylic cleavage in two positions (cf. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhong et al proved that the HO· radicals, peeled from the phenolic structure or generated from radical exchanged reactions, had high concentration and significantly destructive effect during the initial pyrolysis of PR. Our previous study also indicated that the frontier orbitals of HO· and BPF match well and have the potential to react with each other. From the above analyses, it can be speculated that HO· may have destructive effect on the initial decomposition of BPF, and from another perspective, the introduction of HO· maybe effective in degradation of BPF.…”
Section: Introductionmentioning
confidence: 61%
“…The reactivity analyses will be helpful for determining which BPFs or which sites of the BPFs are vulnerable to HO· attack. The main basis of this part are: (i) During the initial stage of hydrogen abstraction or free radical addition reactions, the free radical is firstly attracted by the electrostatic potential; (ii) Frontier orbitals match well is the prerequisite for the title reactions; (iii) When the radicals and target group are close enough, the electron population began to overlap and Fukui function will be more precise to present the reactivity of functional groups …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation